The 90-day Readmission Rate after Single-Bundle ACL Reconstruction Plus LET: Analysis of 2,559 Consecutive Cases from a Single Institution - Grassi, Alberto; Costa, Giuseppe Gianluca; Cialdella, Sergio; Lo Presti, Mirco; Neri, Maria Pia; Zaffagnini, Stefano (The Journal of Knee Surgery, 2020)
The aim of the present study is to examine the readmission rate within 90 days of a cohort of patients, who underwent an arthroscopic anterior cruciate ligament (ACL) reconstruction with a lateral extraarticular tenodesis, from a single highly specialized sports traumatology department. From our institutional database, we identified 2,559 patients (78.5% males and 21.5% females, with a mean age at surgery of 30.9 ± 11.5 years) who underwent primary ACL reconstruction with the same “over-the-top” technique plus lateral extraarticular tenodesis (LET) from January 2010 to December 2017. From this count, we extracted all patients who were readmitted within 90 days and focused on causes of readmission and reoperation rate. Moreover, a multivariate logistic regression was performed to identify possible variables, such as gender, age, and concomitant meniscus surgery, which could predict the risk of early readmission. From the aforementioned cohort, 58 patients (2.27%) were readmitted within 90 days from surgery after a mean time of 31 ± 23 days. The most common cause of readmission was fever and knee swelling (0.78%), followed by superficial infection (0.63%), deep infection (0.55%), and joint stiffness (0.23%). The patients' age and meniscal lesions requiring concomitant arthroscopic treatment were found to be correlated to an increased risk of early readmission. Superficial infections were more common in female patients (odds ratio [OR] = 3.01), whereas the meniscal treatment was also a significant risk factor specifically for deep infections (OR = 3.56). In conclusion, this technique of arthroscopic ACL reconstruction with LET showed a low readmission rate within 90 days from surgery. However, patients and physicians should be aware of the risk of serious complications, such as deep and superficial infections, mostly in female patients and in cases of concurrent meniscal treatments. This is a Level IV, retrospective case series study.
Keywords: anterior cruciate ligament; ACL; anterolateral ligament; lateral extraarticular tenodesis; epidemiology; complications; readmission rate; infection